PERTANGGUNGJAWABAN PIDANA DOKTER YANG TIDAK MELAKUKAN REKAM MEDIS TERHADAP PASIEN (STUDI PUTUSAN PERKARA NOMOR 86/PID.B/2009/PN.LGS) - Paian Tua Dolok Matio Sinaga; Madiasa Ablisar; Marlina Marlina; Chairul Bariah (Universitas Sumatera Utara, 2018)
ABSTRACT A doctor is seen as a very noble profession, so with that assumption, the people involved in sustaining life are seen as noble ones. It shows the form of human dependence on the importance of the existence of doctors in the world of health. Patients have great confidence and expectation of the doctor for the illness, even if they have to pay a lot of money. In fact, there are often mistakes caused by the negligence of doctors in the treatment of patients who do not make a medical record. This causes great disappointment to the world of medicine, the patient becomes lost trust and also cause traumatic effects on doctors. In addition to feeling disappointed patients are also harmed both in health, service and also materially. This study aims to describe and analyze the form of criminal liability doctors who do not record medical patients. Primary data collection is done through legislation and case study dr. Bukhari, Sp.OG which occurred in 2009 in Langsa Aceh. The regulation of medical records on doctors who practice medicine has been regulated clearly in Law No. 29 of 2004 on Medical Practice and Regulation of the Minister of Health No. 269/MENKES/PER/XII/2008 concerning Medical Record. In performing its obligations the doctors should refer to it. So that doctors can be asked for accountability either criminal or civil. The form of criminal liability of a physician who does not perform medical records in the conduct of medical practice based on the Case Decision Study Number 86/Pid.B/2009/PN.LGS states that, the doctor who deliberately did not make a medical record to his patient while carrying out his medical practice in accordance with the Medical Profession Standard so as to be sentenced to the defendant dr. Bukhari Sp.OG with a fine of Rp. 30,000,000 (thirty million rupiahs), stipulates if the fine is not paid then replaced with imprisonment for 3 (three) months. Keywords: Criminal liability, Doctor, Medical Record, and Patient.